North Macedonia interprofessional dementia care (NOMAD) – personalized care plans for people with dementia and caregiver psychoeducation delivered at home by interprofessional teams - Novotni, Gabriela; Taneska, Marija; Novotni, Antoni; Fischer, Julia; Iloski, Svetlana; Ivanovska, Andrea; Dimitrova, Vesna; Novotni, Ljubisha; Milutinović, Miloš; Joksimoski, Boban; Chorbev, Ivan; Hasani, Shpresa; et al. (Frontiers in Dementia, 2024)
The increasing number of people living with dementia and its burden on families and systems particularly in Low-and Middle-Income Countries requires comprehensive and efficient postdiagnostic management. This study aimed to explore the acceptability and efficacy of a multiprofessional case-management and psychoeducation model (NOMAD) delivered by mobile teams for people with dementia and their caregivers in North Macedonia. We conducted a two-arm randomized controlled trial comparing the intervention with treatment as usual. Participants were recruited from 12 GP offices from Skopje region. The NOMAD intervention included delivery of a personalized care plan over 4 home visits to dyads of a people with dementia and their caregivers by a team of dementia nurse and social worker, in collaboration with GPs, dementia expert and introduction of a caregiver manual. We assessed caregivers' depressive symptoms, burden and quality of life and neuropsychiatric symptoms, daily living activities and service utilization of people with dementia at baseline and follow-up, and assessed the acceptability of the intervention by analyzing case-notes and attendance rates. 120 dyads were recruited and randomized to either the control (n=60) or the intervention group (n=60). At follow up, caregivers in the intervention group had on average 2.69 lower depressive symptoms (95% CI: -4.75 to -0.62; p=0.012) and people with dementia had on average 11.32 lower neuropsychiatric symptoms (95%CI: -19.74 to -2.90; p=0.009), used on average 1.81 lower number of healthcare services (95% CI -2.61 to -1.00; p<0.001) compared to the control group. The completion of the home visits was 100% but the intervention's acceptability was underpinned by relationship building and GPs competences and resources in supporting families with dementia. There were no differences in the caregivers' quality of life, burden levels or daily living activities in people with dementia. NOMAD is the first case-management, nonpharmacological and multi-professional intervention tested in N. Macedonia. The trial showed that it is effective in reducing caregivers' depressive symptoms and neuropsychiatric symptoms in people with dementia, the burden on health and social care services and it is acceptable for families. Implementing NOMAD in practice will require building primary care capacity and recognizing dementia as a national priority.